Designing of Agricultural Product e-Marketplace by using UCD Method - Wisti Dwi Septiani; Sri Utami; Octa Pratama Putra; Noer Hikmah; Popon Handayani; Narti Narti (JURNAL TEKNIK KOMPUTER, 2021)
The growth and era of information, communication and technology have changed and it has benefits in various sectors, one of them is the economy aspect. The current sales system has been moved from conventional sales into online sales by utilizing technology as a media for sales transactions. Then, one of them is the presence of e-commerce websites and e-marketplaces. The concept of e-marketplaces is a place where buyers and sellers meet, then they make online buying and selling transactions. However, there are still many plantations whose agricultural products have not been reached to be implemented by the marketplace. This problem is based on the cultural factors; it is called through the broker. Also, as well as the lack of education of farmers. The purpose of this study is to design the e-marketplace for farmers, especially in the Bugis Village. The user-centered method is applied where the approach is centered on users, then both consumers and partners. The website-designed is made by looking at the needs of the user side. This e-marketplaces can also be an education for businesses in the field of agricultural products. It is also to be involved in technological advancements by becoming partners in the e-marketplaces, so that they are able to market their products through online system. In addition, to minimize the use of agricultural products by broker, too. The results of this study are e-marketplace is able to provide convenient websites for users in conducting transactions by using gadgets to access agricultural products. This e-marketplaces also supports the promotion of Go Green, which has begun to implement a healthy lifestyle; by starting to consume a lot of vegetables. So, people will easily get best quality of agricultural products from farmers.